Animal Imagery in George Orwell's novel “Animal Farm” - Sushil Ghimire, (Journal of Balkumari College, 2022)
The present paper is a literary stylistic study that illustrates in George Orwell's novel Animal Farm the imagery, the allegorical meaning, linguistic exploitation or manipulation of words. One of the most traditional features of the Animal Farm and an integral part of its imagery is Orwell 's sophisticated sensitivity to political abuse of language Inwardly, this novel is an allegory that relates to power struggle, usurpation, coercion, manipulation, hypocrisy, oppression, political racket and fear of the ruling classes in any shape they may exist (human or animal). It seems to be a simple tale of animals. However severe the subject is, through his vivid imagery and artful use of literary instruments, Orwell has made it imaginative and humorous. With its clear, deceptively simple, but creatively honed prose style and expressive language, the novel is a source of great aesthetic and intellectual pleasure and political insight.